Self-Concept of Teens Living in an Orphanage - Fera Handayani Safitri; Riska Ahmad (Jurnal Neo Konseling, 2021)
This research is motivated by the phenomenon that the existence of adolescents who have a low self-concept from the physical aspects such as adolescents feeling not beautiful, and social aspects such as feeling disliked by their friends, and emotional aspects such as feeling unhappy, and moral aspects such as being often dishonest. and cognitive aspects such as feeling unable to complete a task well. This study aims to describe the self-concept of adolescents living in the orphanage 'Aisyiyah, Koto Tangah branch, Padang. This research is a type of quantitative research with descriptive methods. The subjects of this study were 20 junior high school adolescents. The instrument used in collecting research data was a questionnaire. Data were analyzed using descriptive statistical techniques. The results showed that (1) adolescent self-concept in terms of physical aspects was in the low category with a percentage of 60%, (2) adolescent self-concept in terms of social aspects was in the medium category with a percentage of 40%, (3) adolescent self-concept which in terms of emotional aspects are in the low category with a percentage of 50%, (4) adolescent self-concept in terms of moral aspects is in the low category with a percentage of 65%, and (5) adolescent self-concept in terms of cognitive aspects is in the low category with a percentage of 55%. Based on the research findings, it is highly recommended that the board of the orphanage pay more attention to the self-concept of adolescents living in the orphanage by carrying out activities that lead to the creation of good and positive self-concepts in children in their developmental stages.